Digital Economy and Digital Twins. Main Research Area - Meytus, V.Yu.; Morozova, G.I.; Taran, L.Yu.; Kozlova, V.P.; Maidaniuk, N.V. (Control systems & computers, 2020)
The work is devoted to the consideration and research of methods for transforming economic structures that underlie the transition to the dominant digital task of economic processes and their relationship with digital forms of representing economic relations. The main stages of the possible assignment of enterprises and the levels of building digital twins have been determined. Using the example of an object that belongs to the external area of ​​the enterprise – the supplier of the constituent components of the product – it is shown how the transition to the digital form of this object can be built.